History in the making things to come - Mills, John, Sir; Sidaway, Ashley; Sidaway, Robert; Sellar, Maurice (Herts : Screen Entertainment, 1991)
Things to come, presents past and future are thrown into confusion by human invention and curiosity. The mysterious world of science, scientists and science fiction has always intrigued audiences and film-makers alike
History in the making, looks at how British films have delved into the annals of history and produced their own cinematic version of events, great disaster, great romances and the splendour of great courts
Title from data sheet
Narrated by John Mills
Keywords: Motion pictures and history; Motion pictures -- United Kingdom -- History; Motion pictures in science